Peran Taman Pendidikan Al-Qur’an Nurul Huda Pagiri Pondok Aren Tangerang Selatan Dalam Mengembangkan Kemampuan Baca Tulis Al-Qur’an - Mutuanisa Mahda Rena; Miratul Hayati (STIT Muslim Asia Afrika, 2021)
The purpose of this research is to explore the learning activities of The Qur'an Education Park Nurul Huda Parigi Baru Pondok Aren Tangerang Selatan in developing children's Qur'anic reading skills, use of methods, and learning processes. The method used in this study is the decryptive method of analysis. The subject of this study was a parent who had a child aged 4-6 years who participated in the Activities of Reading The Qur'an in the Education Park of the Qur'an Nurul Huda Parigi Baru Pondok Aren South Tangerang. Data is collected using interview instruments conducted with parents and teachers, as well as observations and documentation to support the required data. It can be known that the role of the Qur'an education park in developing the ability to read the Qur'an in the Nurul Huda Parigi Baru Pondok Aren Education Park, South Tangerang is very well developed. Through the Qur'anic Education Park children are able to read hijaiyah letters using the Iqro' method, able to write Arabic letters by imla method, able to read short surahs in the Qur'an, and able to memorize readings in prayer.